Nonspecific food dependant exercise-induced anaphylaxis with seizure: a case report - Karadan, Ummer; Manappallil, Robin George; Zacharia, Ivin Panakkel; Anand, Thushara (Asian Journal of Medical Sciences, 2020)
Exercise has been associated with several systemic reactions. These reactions can vary from mild symptoms to life threatening situations like anaphylaxis. In many of these cases, a predisposing factor in the form of food has been noticed. People may develop anaphylaxis on exercising after consumption of a nonspecific or specific food item. The patient being described developed anaphylaxis with seizure on exercising after having his meal. Nonspecific food dependant exercise-induced anaphylaxis is a rare scenario. Proper history taking is essential, as it can be lifesaving.